Inhibition of soluble epoxide hydrolase is renoprotective in 5/6 nephrectomized Ren‐2 transgenic hypertensive rats. (March 2014) - Kujal, Petr; Čertíková Chábová, Vera; Škaroupková, Petra; Husková, Zuzana; Vernerová, Zdena; Kramer, Herbert J; Walkowska, Agnieszka; Kompanowska‐Jezierska, Elzbieta; Sadowski, Janusz; Kitada, Kento; Nishiyama, Akira; Hwang, Sung H; et al.
Summary The aim of the present study was to test the hypothesis that increasing kidney tissue concentrations of epoxyeicosatrienoic acids (EETs) by preventing their degradation to the biologically inactive dihydroxyeicosatrienoic acids (DHETEs) using blockade of soluble epoxide hydrolase (sEH) would attenuate the progression of chronic kidney disease (CKD). Ren‐2 transgenic rats (TGR) after 5/6 renal mass reduction (5/6 NX) served as a model of CKD associated with angiotensin (Ang) II‐dependent hypertension. Soluble epoxide hydrolase was inhibited using cis‐4‐[4‐(3‐adamantan‐1‐yl‐ureido)cyclohexyloxy]benzoic acid (c‐AUCB; 3 mg/L drinking water) for 20 weeks after 5/6 NX. Sham‐operated normotensive transgene‐negative Hannover Sprague‐Dawley (HanSD) rats served as controls. When applied in TGR subjected to 5/6 NX, c‐AUCB treatment improved survival rate, prevented the increase in blood pressure, retarded the progression of cardiac hypertrophy, reduced proteinuria and the degree of glomerular and tubulointerstitial injury and reduced glomerular volume. All these organ‐protective actions were associated with normalization of the intrarenal EETs : DHETEs ratio, an index of the availability of biologically active EETs, to levels observed in sham‐operated HanSD rats. There were no significant concurrent changes of increased intrarenal AngII content. Together, these results show that 5/6 NX TGR exhibit a profound deficiency of intrarenal availability of active epoxygenase metabolites (EETs), which probably contributes to the progression of CKD in this model of AngII‐dependent hypertension, and that restoration of intrarenal availability of EETs using long‐term c‐AUCB treatment exhibits substantial renoprotective actions.